Attitude of Smoker and Non-Smoker Libyan Dentists Towards Smoking Cessation - Alayan, Khaled Mohamed; Rhab, Mohamed; Rahab, Abdulmutalib Mohamed; Mohamed, Abubakr Omar (Med Phoenix, 2019)
Abstracts available on full text.